Stability of Characterizing Properties of Exponential Distribution - Azlarov, T. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Т. Азларов. Устойчивость характеризационных свойств показательного распределения T. Azlarovas. Eksponentinį pasiskirstymą charakterizuojančių savybių stabilumas